Analysis Of Marketing Strategies To Improve The Competitiveness Of MSMEs (Study On Convection Maketees) - Reza Fahlevy; Agus Rahayu; Puspo Dewi Dirgantari (Dinasti Publisher, 2025)
Marketing strategy is very important to the operation of a company in which the existence of a marketing strategy, the business run by the company has long-term actions which have a way to achieve the company's goals so that it is more directed, planned and prepared more carefully so that the intended target can be achieved, and can also anticipate all occurs in the target market. This study aims to determine the overview of marketing strategies to improve competitiveness, and to determine how effective the implementation of marketing strategies that have been done. The study was conducted in convection Maketees. Data collection techniques with interviews, observations, and documentation, descriptive type of research. The results of the analysis of the effectiveness of marketing strategies showed an increase in revenue from year to year and serve as a reference for the effectiveness of marketing strategies in competition between convection.